2021
DOI: 10.1111/1541-4337.12721
|View full text |Cite
|
Sign up to set email alerts
|

Meat analogs: Protein restructuring during thermomechanical processing

Abstract: Increasing awareness of inefficient meat production and its future impact on global food security has led the food industry to look for a sustainable approach. Meat products have superior sensorial perception, because of their molecular composition and fibrous structure. Current understanding in the science of food structuring has enabled the utilization of alternative or nonmeat protein ingredients to create novel structured matrices that could resemble the textural functionality of real meat. The physicochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 165 publications
1
70
0
1
Order By: Relevance
“…Pea protein is commonly used in the manufacturing of meat analogues [ 3 , 36 ]. Therefore, it is relevant to mention that the overall free amino N (%) values released during digestion of PPI were lower than that usually observed for meat [ 2 , 22 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pea protein is commonly used in the manufacturing of meat analogues [ 3 , 36 ]. Therefore, it is relevant to mention that the overall free amino N (%) values released during digestion of PPI were lower than that usually observed for meat [ 2 , 22 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The fibrous structuring of plant proteins using thermomechanical processing can be classified under two main principles. The first principle is based on phase separation within a multi-phase protein mixture [218,219]. The dispersed phase acquires a spherical droplet morphology under interfacial tension and undergoes deformation-elongationsolidification to form anisotropic structures in the direction of the applied shear [220,221].…”
Section: Formation Of Fibrous Structuresmentioning
confidence: 99%
“…Meanwhile, the hydrophobic and free SH groups that were initially buried inside the native protein are exposed. The shearing from the extrusion aligns the uncoiled protein molecules in the direction of flow, resulting in a three-dimensional network structure [218]. The texturization phase inside the cooling die initiates the solidification and formation of fibrous structure through the inter-and intra-molecular aggregation of the proteins.…”
Section: Formation Of Fibrous Structuresmentioning
confidence: 99%
“…The right proportion of lipids can effectively increase moisture retention in simulated fat, thereby improving the tenderness, texture and juiciness of recombinant plant-based meat alternatives [ 85 ]. In one recent study, 3.5% sunflower oil and konjac glucomannan were used as raw materials to develop a plant-based fishball analogue, the results of which showed that the addition of sunflower oil is beneficial to the texture and water retention of plant-based fishballs [ 86 ].…”
Section: Factors Affecting the Structural Quality Of Simulated Fatmentioning
confidence: 99%